G600(P) Designing a care pathway for a modern Neurodevelopmental Service. (27th April 2016) - Waheed, S; Maharaj, N
Abstract : Aims: To review first appointments for all new patients seen in the neurodevelopmental service over 12 months to identify if there was any variation in practice between the four clinicians (senior registrar or above) delivering the service and whether there is evidence that the service can be front loaded offering a more cost effective service with increased patient satisfaction. Methods: The online patient records were reviewed for all new patients seen in 12 months (2013/14). For each patient's first appointment, the reviewing clinician, the referrer, investigations offered, referrals made, suspected diagnosis and discharge outcome was captured. Results: There were 270 referrals seen. Patients were aged between 18 months to 10 years. At first appointment, 24% of patients were investigated with a range of 10% to 42% between clinicians (Figure 1 ). 50% of patients were discharged with a range of 19% to 81% between clinicians (Figure 2 ). 31% of patients had multiple or single referrals made at first appointment (Table 1 ). The average waiting time to be seen was 74 days (range 59–86 days). Conclusions: The results show that there was a wide variation in practice between clinicians across the unit in terms of investigations and discharge rates with one of the four clinicians more likely to offer investigations and to discharge after first appointment. This demonstrates the need for a robust pathway with new guidelines rationalising investigations and follow-up criteria based on best practice to ensure that there is uniformity between clinicians at first appointment. The evidence also demonstrates that it is viable to move to a front loaded one stop shop approach for the majority of patients whereby patients are investigated and referred and subsequently discharged at first appointment. With each first appointment taking 60 to 90 min with an average waiting time of at least 10 weeks then early discharge would decrease waiting times, increase patient satisfaction and be more cost- effective.